Mycobacterial avium intracellulare (MAI) extensor tenosynovitis of wrist: An uncommon entity - Vishal Kalia; Gregory Garvin; Yi Yan; Vibhuti Kalia (Radiology Case Reports)
Rice bodies secondary to synovial inflammation, typically occur in the shoulders and knees of individuals affected by either rheumatoid arthritis or tuberculosis. It is uncommon to encounter these in nontubercular mycobacterial tenosynovitis especially in wrist extensor compartment. Understanding this condition and its distinctive imaging features is crucial for both treating clinicians and radiologists. In this case study, we present the imaging findings of a rare occurrence of tenosynovitis of the fourth extensor compartment in the wrist with the formation of rice bodies due to Mycobacterium avium intracellulare. We have chosen to document this case to emphasize its importance in considering the differential diagnosis of extensor tenosynovitis with rice bodies.